De la Responsabilité sociale des organisations à l’achat public responsable : entre contraintes et performances. Compte rendu de journée d’étude - Olivier Gayot (Développement Durable et Territoires)
Responsible public procurement can be understood as a new conception of public procurement, which could reaffirm the role of public actors in the institutionalization of sustainable development, especially on a territorial scale. There is nearly no academic literature in economics about responsible public procurement, as the concept is rather recent. The point of this article is to present several practical and theoretical perspectives around responsible public procurement, not pretending to any form of exhaustiveness. These perspectives were discussed during a study day organized within the RSECO project « CSR and public procurement, between constraints and performances » which took place on November 23rd, 2017 at the MESHS (Lille, France).